Dissolution enhancement of poorly soluble drug by solvent evaporation method using hydrophilic polymer: a solid dispersion technique - Minhaz, Md Armin; Rahman, Md Mofizur; Ahsan, Md Qamnul; Khalipha, Abul Bashar Ripon; Chowdhury, Mohammed Raihan (International Journal of Pharmaceutical and Life Sciences, 2012)
In order to investigate the effect of polymers on release mechanism of poorly soluble drugs from solid dispersions, Clonazepam was used as a model drug for these purposes. Five types of solid dispersions were prepared using polyethylene glycol 6000 (PEG- 6000), Kollicoat IR, Kollidon VA 64 and Poloxomer in different drug-tocarrier ratios (1:2, 1:4, 1:6, 1:8, 1:10). The solvent evaporation method was used for preparation of solid dispersions. The in-vitro dissolution study with temperature of 37° C and a paddle method, 100 rpm was used in 1000 ml of distilled water as dissolution medium in each dissolution basket for the pure drug and solid dispersions. For pure Clonazepam showed very slow dissolution rate and the solid dispersion considerably enhanced the dissolution rate. Decreased crystalline and increased amorphous fraction of the drug was probably done by wettability and dispersibility. The highest improvement in wettability and dissolution rate of Clonazepam was observed in PEG-6000, Poloxomer and Kollidon VA 64 (1:10 ratio). Solid dispersions containing polymer (1:10 ratio) prepared by solvent method showed significant improvement in the release profile as compared to pure drug, Clonazepam. DOI: http://dx.doi.org/10.3329/ijpls.v1i2.12952 International Journal of Pharmaceutical and Life Sciences Vol.1(2) 2012